Longitudinal investigation of the role of Streptococcus mutans in human fissure decay. - Loesche, W J (1979)
A prospective study was initiated in order to detect changes in the levels and proportions of Streptococcus mutans, S. sanguis, and lactobacilli before and at the time of caries development on occlusal fissures. The bacteriological analysis was performed on 195 teeth that received four examinations at approximately 6-month intervals. The data obtained from 42 carious fissures and 153 caries-free fissures strongly indicated an etiological role for S. mutans in most of the diagnosed fissure lesions. This was demonstrated by the longitudinal analysis, which showed the proportions of S. mutans to increase significantly at the time of caries diagnosis, and by cross-sectional comparisons, which showed that the proportions of S. mutans in the carious fissures were significantly higher than in caries-free fissures. Three subjects who had a low caries expereince developed five new carious lesions. Lactobacilli were prominent members of the caries-associated flora in these subjects greatly outnumbering S. mutans. The levels and proportions of S. sanguis tended to be higher in the caries-free fissures. Altho1gh the results are striking in that they implicate S. mutans in fissure decay, they show that clinical decay can occur in a few instances in the absence of detectable S. mutans, as was observed in the fissures high in lactobacilli.